Brand coolness part two for Mexico city´s Group - Loureiro, S. M. C. (invitation as guest speaker for MBA at Mexico city´s Group, 2021)
HOW cool is a brand? Insights about the ten dimensions of brand coolness The case of Portuguese brands. Discussion niche and mass coolness.